Pengaruh Profitabilitas, Likuiditas, Struktur Aktiva, Ukuran Perusahaan, dan Tax Avoidance Terhadap Struktur Modal - Muhammad Efendi; Kartika Hendra Titisari; Suhendro Suhendro (Universitas Batanghari Jambi, 2021)
This study aims to determine the effect of profitability, liquidity, asset structure, company size, and tax avoidance on capital structure. The population in this study is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) 2016-2019. The sample was selected from the purposive sampling method and got a sample of 10 companies from several criteria. The data source is secondary data from the website www.idx.co.id. This research uses multiple linear regression analysis. The results of this research indicate that profitability affects the capital structure. Meanwhile, liquidity, asset structure, company size and tax avoidance have no effect on capital structure.